2020
DOI: 10.1021/acs.cgd.0c01312
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Continuous Crystallization and Spray Drying of Insulin for Pulmonary Drug Delivery

Abstract: Pulmonary delivery of insulin in the form of a dry powder is an attractive alternative in comparison to conventional subcutaneous delivery. Insulin crystals have potential advantages such as sustained release and higher stability in comparison to amorphous particles. However, the design of crystallization processes that can reliably produce insulin crystals in a suitable size range for pulmonary delivery is challenging. A continuous process involving the integration of a tubular crystallizer and a spray dryer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Chen et al. [ 24 ] have demonstrated the influence of various parameters on the mean particle size and insulin recovery of a CSFC. The parameters varied were: pH, initial insulin concentration, and gas and liquid flow rates.…”
Section: Recent Experiments In Protein Crystallizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al. [ 24 ] have demonstrated the influence of various parameters on the mean particle size and insulin recovery of a CSFC. The parameters varied were: pH, initial insulin concentration, and gas and liquid flow rates.…”
Section: Recent Experiments In Protein Crystallizationmentioning
confidence: 99%
“…Gas is injected into the stream at regular intervals to make small packets of solution. [21][22][23][24] The shearing of liquid with the walls causes circulation, which helps ensure a uniform supersaturation while also preventing deposition and clogging to some extent. Clogging may still occur due to the smaller internal tube diameter and the lack of other agitation sources.…”
Section: Slug Flow Crystallizer (Sfc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting larger mean MMAD is attributed to the increased solute content in each atomized droplet, leading to an increased feed viscosity and enlarged primary particle size [87]. This positive effect could also result from a stronger propensity for particle agglomeration at a high degree of local supersaturation [76,88,89]. A low solute concentration imparts long interparticle distance with diffused nuclei, thereby minimizing agglomeration, which is favorable to pulmonary drug delivery.…”
Section: Identification Of Influential Factors For the Critical Quali...mentioning
confidence: 99%
“…In practice, harvest broth from biotechnological processes involves mixtures of proteins, impurities, and only a small quantity of the target molecule. While a lot of research was reported on scaled-up protein crystallization in solutions containing only traces of impurities or even none ( Judge et al, 1995 ; Lee et al, 2000 ; Peters et al, 2005 ; Hebel et al, 2013 ; Yang et al, 2019 ; Chen et al, 2021 ; Tian et al, 2023 ; Jul-Jørgensen et al, 2024 ), the challenges imposed by complex solutions in capture processes have received relatively little attention ( Takakura et al, 2006 ; Smejkal et al, 2013 ; Hekmat et al, 2017 ; Grob et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%